Application of HACCP Principles to Local Drying Processes of Capsicum Species in Bolivia and Peru - Salvatierra Rojas, Ana; Nagle, Marcus; Argyropoulos, Dimitrios; Ríos Lobo, Llermé; Serrano Quintanilla, Edwin; Bejarano Martinez, Carlos; Jäger, Matthias; Mueller, Joachin (ResearchGate, 2020)
The aims of the proposed research were to identify and document species, production and uses, describe processing procedures for drying, evaluate drying conditions and practices and apply Hazard Analysis and Critical Control Point (HACCP) principles to identify the critical control points involved in drying processes. The study focused on cultivated species of capsicum in the areas around Chuquisaca, Bolivia and Lima, Peru under the guidance of local partners. Farmer interviews were conducted to obtain information about current postharvest handling practices. In addition, drying procedures were evaluated at several sites. Parameters were documented, including drying conditions and behaviour of the product by placing climate sensors in the drying bulks and sampling and analysing the product at significant processing points. Based on this data, HACCP principles were applied, namely: product description, identification of intended uses, construction and confirmation of flow diagrams, list potential hazards, hazard analysis and consideration of control measures, establishment of critical control points based on Codex Alimentarius and establishment of critical limits. Recommendations are given as a baseline for the complete implementation HACCP standards corresponding to the monitoring of the production chain to ensure food safety. Corrective actions can now be implemented via verification procedures and documentation and record keeping will allow realisation of HACCP quality assurance for the production of dried Capsicum in Bolivia and Peru.